PENGARUH TENAGA KERJA DAN TINGKAT PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAWA TIMUR TAHUN 2018 - Alie Sadikin; Turnadi Turnadi (Institut Bisnis Muhammadiyah Bekasi, 2022)
The study determines the effect of labor, and education partially, and simultaneously of economic growth in East Java Province in the period of 2018. Samples were taken using the entire population in East Java Province, which includes 38 cities and regencies in East Java. Descriptive statistics is, a classical assumption test, hypothesis testing, multiple linear regression test, and the coefficient of determination test is a data analysis. The results of this study conclude that with the obtained value of 6.037+(-0.025)X1+0.078X2 with a constant value of 6.037, it can be concluded that the labor variable has an impact on the Y variable. And the education variable has a positive relationship with Y, the lower the value of the workforce. employment means the lower value of Economic Growth (Y). And the higher the value of education, the higher the economic growth (Y).